Design of Acoustic Tubes Array and Application to Measuring Acoustic Loads in Supersonic Airflow - WEI, Long; LI, Min; FU, Qiang; FAN, Yue; YANG, Debin (Archives of Acoustics, 2014)
In the acoustic fatigue experiment for hypersonic vehicle in simulated harsh service environment on ground, acoustic loads on the surface of test pieces of the vehicle need to be measured. However, for the normal microphones without high temperature resistance ability, the near field sound measurement cannot be achieved. On the basis of previous researches, in this work, an acoustic tubes array is designed to achieve the near field measurement of acoustic loads on the surface of the test piece in the supersonic airflow with high temperature made by coherent jet oxygen lance. In this work, the process of designing this acoustic tubes array is firstly introduced. Then the equivalence between phase differences of microphones mounted at exit of tubes and those at entrances of tubes are proved, which ensure the reasonability of substituting the phase differences of signals acquired by microphones directly into beamforming algorithm to acquire the distribution and intensity of the acoustic load source. Finally, with this designed acoustic tubes array, a measurement of acoustic loads on the surface of the test piece in the supersonic airflow made by coherent jet oxygen lance is conducted, and the measurement result is analyzed.